2013
DOI: 10.3174/ajnr.a3781
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Middle Cerebral Artery Aneurysms for 120 Nonselected Patients: A Prospective Cohort Study

Abstract: BACKGROUND AND PURPOSE:Multiple technologies have developed the endovascular approach to MCA aneurysms. We assess the safety and the efficacy of a systematic endovascular approach in nonselected patients with MCA aneurysms and determine predictors of treatment outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
27
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 26 publications
3
27
1
3
Order By: Relevance
“…In a recent prospective cohort of 131 consecutive nonselected MCA aneurysms (34.2% ruptured aneurysms), balloon assistance was required in 60.3%. 4 As previously reported, the balloon-assisted coiling technique does not seem to increase the complication rate compared with simple coiling in unruptured and ruptured aneurysms. 4,10 Similar results concerning safety have also been reported by using stent-assisted coiling of wide-neck aneurysms.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…In a recent prospective cohort of 131 consecutive nonselected MCA aneurysms (34.2% ruptured aneurysms), balloon assistance was required in 60.3%. 4 As previously reported, the balloon-assisted coiling technique does not seem to increase the complication rate compared with simple coiling in unruptured and ruptured aneurysms. 4,10 Similar results concerning safety have also been reported by using stent-assisted coiling of wide-neck aneurysms.…”
Section: Discussionmentioning
confidence: 51%
“…2,3 Balloon and stentassisted techniques have widened the indications for endovascular treatment of MCA aneurysms with a wide neck and/or unfavorable anatomy that were otherwise unsuitable for coiling. 4,5 However, the risk of procedure-related morbidity and mortality is not negligible, especially with double-stent placement in Y and X configurations. 4,6,7 The widespread adoption of endovascular treatment for MCA aneurysms with unfavorable anatomy requires an improvement of the safety of the endovascular approach.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The retreatment rate reported for basilar bifurcation aneurysms ranges between 15% and 27.8%, [18][19][20] and for MCA bifurcation aneurysms, it has been reported in up to 7.6% of patients. 21 The increased hemodynamic stress at the level of arterial bifurcations has been linked to the development of aneurysms 5,22 and certainly has a role in the recurrence seen after endovascular treatment. Most interesting, some aneurysms were found to have recurred even after stable follow-up imaging 6 or 12 months after initial treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Balloon and stent-assisted techniques have widened the indications for endovascular treatment of aneurysms with a wide neck and/or unfavorable anatomy that were otherwise unsuitable for coiling. [8][9][10] However, endovascular treatment of such complex intracranial aneurysms requires the use of complex endovascular techniques with double-stent placement in Y and X configurations. Bartolini et al 11 suggested that Y and X stent-assisted coiling was associated with a high rate of complications, 10% procedure-related permanent morbidity, and 1% mortality rate.…”
mentioning
confidence: 99%